Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2298/pac1302081r
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric, impedance, electric modulus and AC conductivity studies on (Bi0.5Na0.5)0.95Ba0.05TiO3 ceramic

Abstract: Lead-free piezoelectric perovskite ceramic (Bi0.5Na0.5)0.95Ba0.05TiO3 (BNT-BT0.05), prepared by conventional high temperature solid state reaction technique at 1160 °C/3h in air atmosphere, is investigated by impedance and modulus spectroscopy in a temperature range 35–400 °C, over a frequency range 100 Hz–1 MHz. The crystal structure, microstructure, and piezoelectric properties as well as the AC conductivity of the sample were studied. Powder X-ray diffraction pattern derived from the resulting data at the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Additionally, the exponent s 2 in all the samples reached a minimum at ~400ºC, which was the onset of the sharp rise in temperature-dependent dielectric loss curves (Fig. Within the same temperature region, E a reduced with frequency, which is also observed in other systems [48,62]. Within the same temperature region, E a reduced with frequency, which is also observed in other systems [48,62].…”
Section: Ac Conductivitysupporting
confidence: 63%
“…Additionally, the exponent s 2 in all the samples reached a minimum at ~400ºC, which was the onset of the sharp rise in temperature-dependent dielectric loss curves (Fig. Within the same temperature region, E a reduced with frequency, which is also observed in other systems [48,62]. Within the same temperature region, E a reduced with frequency, which is also observed in other systems [48,62].…”
Section: Ac Conductivitysupporting
confidence: 63%
“…The increment in s 1 with increasing of OMP may be due to the enhancement in the short‐range hopping process, which corresponds to the grain‐boundary conduction. However, the reduction in s 2 value with an increase in OMP can be attributed to the reduction in charge defects presented in the samples …”
Section: Resultsmentioning
confidence: 98%
“…We now consider a situation where, apart from DC conductivity σ ο , two dielectric loss mechanisms are also present: the first one at the low frequency regime having a characteristic frequency,  minimum, the high frequencies slope can take values higher than 1. It is observed that, with decreasing value of the shape parameter α, the superlinear value of the apparent n exponent, which is calculated in the frequency range of the one order of magnitude lower 16 than HN f , gradually decreases. The high frequencies slope of the AC conductivity is mainly formed from the contribution of slower components of the molecular dipolar relaxation at this frequency range.…”
Section: Resultsmentioning
confidence: 93%